Childhood exposure to armed conflict and nutritional health outcomes in Nigeria - Olusesan Ayodeji Makinde; Emmanuel Olamijuwon; Ifeanyi Mgbachi; Ryoko Sato (Conflict and Health, 2023)
Abstract Background Armed conflicts are associated with an increased risk of food insecurity, the leading cause of malnutrition in low-and-middle-income countries. Multiple studies have uncovered significant influences of childhood malnutrition on children’s overall health and development. As a result, it is increasingly important to understand how childhood experience of armed conflict intersects with childhood malnutrition in conflict-prone countries like Nigeria. This study examined the association between different measures of childhood experiences of armed conflicts and the nutritional health outcomes of children aged 36–59 months. Methods We used data from the Nigeria Demographic and Health Survey linked with Uppsala Conflict Data Program Geo-Referenced Events Dataset using geographic identifiers. Multilevel regression models were fitted on a sample of 4226 children aged 36–59 months. Results The prevalence of stunting, underweight and wasting was 35%, 20% and 3%, respectively. Armed conflicts were mostly recorded in the North-eastern states of Borno (222 episodes) and Adamawa (24 episodes). Exposure to armed conflicts ranged from 0 (no experience of armed conflict) to 3.75 conflicts per month since the child’s birth. An increase in the frequency of armed conflicts is associated with increased odds of childhood stunting [AOR = 2.52, 95%CI: 1.96–3.25] and underweight [AOR = 2.33, 95%CI: 1.19–4.59] but not wasting. The intensity of armed conflict was only marginally associated with stunting and underweight but not wasting. Longer conflicts that occurred in the last year were also associated with the odds of stunting [AOR = 1.25, 95%CI: 1.17–1.33] and underweight [AOR = 1.19, 95%CI: 1.11–1.26] but not wasting. Conclusion Childhood exposure to armed conflict is associated with long-term malnutrition in children aged 36–59 months in Nigeria. Strategies that aim to end childhood malnutrition could target children exposed to armed conflicts.